Does Tolling Per Kilometre Compensate for the External Costs of Trucks? A Geographical Approach for Belgium. (July 2023) - Adam, Arnaud; Proost, Stef; Thomas, Isabelle
Using detailed Global Navigation Satellite System tracing data emitted by all trucks having a gross vehicle weight of over 3.5 tons in Belgium, this paper assesses the efficiency of the current Belgian distance tax system by analyzing its spatial coverage and the matching of the distance taxes with the external costs, globally and locally. Specifically, three research questions are addressed. First, how well do the present charge rates match with external costs? Second, the operationalization of the system requires a good spatial coverage of truck movements. Does the present system guarantee an almost universal coverage? Third, do the distance charges match the external costs? We find that if the distance tax scheme differentiates regionally, it still misses large variations in noise costs. The current tracing infrastructure also captures only part of the truck operations on the territory. If distance tolls for trucks remain the backbone of the taxation of truck operations, it then needs further refinement in time and space if one wants it to be the major tool to correct for the external costs.